Evaluating the Growth Performance of Three Fast-Growing Species in Coal Mine Reclaimation in Aceh : Evaluasi Kinerja Pertumbuhan Tiga Spesies Pohon Cepat Tumbuh pada Lahan Reklamasi Tambang Batu Bara di Aceh - Kusuma, Yosie Syadza; Riharja. TJ, Yuni Septia; Arlita, Tuti; Rosita, Ida; Wijaya, Laila (JURNAL HUTAN TROPIKA, 2025)
Coal mining plays a crucial role in global energy production and regional development, including in Aceh, Indonesia, where operations such as PT. Mifa Bersaudara contribute to energy supply and employment. This study evaluated the revegetation success of three fast-growing species (Falcataria moluccana, Enterolobium cyclocarpum, and Gmelina arborea) in post-mining reclamation areas planted in 2017 and 2018. Planting was performed at a uniform spacing of 4 × 4 m across 27 plots (8 in 2017, 19 in 2018), each measuring 20 × 20 m and containing 25 trees per plot, with a sampling intensity of 3%. Analyzed using descriptive statistics, two-way ANOVA with Tukey HSD, t-test, and Wilcoxon rank-sum tests. Results showed F. moluccana achieved the highest height (17.53 ± 24.75 m in 2017; 10.73 ± 2.88 m in 2018) and diameter (22.25 ± 8.12 cm in 2017; 31.84 ± 11.59 cm in 2018), followed by E. cyclocarpum, while G. arborea grew more slowly. Survival rates of the planted trees remained relatively high in both planting years, with 80.0 ± 19.0% in 2017 and 70.2 ± 16.9% in 2018, and statistical analysis indicated no significant difference between the two years. Fast-growing species enhanced canopy cover, soil stabilization, and microhabitats, supporting slower-growing species, and their combination is recommended to optimize short-term revegetation success and long-term ecosystem resilience in degraded areas.